Building Elliptic Curve Cryptography With Public Key To Encrypt Vietnamese Text - Trung, Mai Manh; Do, Le Phe; Tuan, Do Trung (Journal of Science and Technology on Information security, 2022)
Abstract— Today, Elliptic Curve Cryptography (ECC) has many practical applications. ECC was a direction in lightweight primitive cryptography. This paper is based on the arithmetic idea of an Elliptic curve. Elliptic curve arithmetic can be used to develop Elliptic curve encryption schemes such as key exchange, encryption, and digital signature. Compared with traditional cryptosystems with the same level of security, Elliptic curve cryptography has a smaller key size, reducing processing costs. To encode the Vietnamese text, we are based on the sound of Vietnamese characters to make a table of these characters’ order. In the present paper, we apply a new encryption algorithm with a public key using an Elliptic curve over finite fields on our proposed Elliptic curve equation.